2019
DOI: 10.1007/s42452-019-0377-8
|View full text |Cite
|
Sign up to set email alerts
|

Removal of cadmium (Cd-II) from aqueous solution using gas industry-based adsorbent

Abstract: The present study is to determine the potential of gas industry sludge as a low-cost adsorbent for the removal of cadmium from aqueous solution. The batch experiments were conducted to optimize pH, contact time, adsorbent dose and initial metal ion concentration. The experiments were optimized at pH 5, contact time 60 min and an adsorbent dose of 0.75 g/100 ml with constant agitation at the room temperature. The result of batch experiment was further discussed for the removal of cadmium from adsorbent. The ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…(9) where C o is the initial metal concentration (mg/L) and b is the Langmuir constant (L/mg). If R L > 1, then the adsorption is unfavorable; if R L = 1, then the adsorption is linear; if 0 < R L < 1, then the adsorption is favorable; and if R L = 0, it is irreversible [11].…”
Section: Adsorption Isothermmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) where C o is the initial metal concentration (mg/L) and b is the Langmuir constant (L/mg). If R L > 1, then the adsorption is unfavorable; if R L = 1, then the adsorption is linear; if 0 < R L < 1, then the adsorption is favorable; and if R L = 0, it is irreversible [11].…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Adsorption has been an important area of interest in the recent years, with majority latest research focused on identifying low-cost adsorbents [9]. Research work is also being done to synthesize new adsorbents with some recent advances in novel adsorbents which include using activated carbon synthesized from peanut shell [10], alizarin red-S-loaded amberlite IRA-400 anion exchange resin [11], starch/SnO 2 nanocomposite [12], Fe 3 O 4 nanocomposites [13], MOF (metal organic framework)-based composites [14,15], nickel ferrite bearing nitrogen-doped mesoporous carbon (NiFe 2 O 4 -NC) [16], nanocomposite cation exchanger sodium dodecyl sulfate acrylamide Zr(IV) selenite (SDS-AZS) [17] for removing toxic heavy metals. Such adsorbents are specially tailored to give them favorable properties like high adsorption capacity, regeneration capability, high surface area, mechanical and thermal stability [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the obnoxious materials that stay in water bodies for a longtime period bring changes in the physiochemical characteristics as well as the natural scenario of the lakes [5]. The Himalayan lakes are under stress due to mismanaged human activities, which increase nutrients and pollution in terms of heavy metals toxicity and bacterial contamination [6][7][8]. The management and preservation of the lakes at present have become a great challenge for environmentalists and managers [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…The probable reason mentioned was the agglomeration of the adsorbent at higher concentrations which inhibits the adsorption process due to surface adsorption decrease. In fact, in another study an increase in the removal efficiency of Cd 2+ ions (83% to 89%) was observed when the concentration of gas industry-based adsorbent was increased from 0.25-1.25 g/100 ML [34]. In gas phase, it was found that no agglomeration takes place, so the adsorption only depends on the amount of adsorbent added.…”
Section: Nanomaterials Applied For the Removal Of Metallic Ions From Watermentioning
confidence: 94%